Caracterização de germoplasma, herança e identificação de marcadores SNP associados à resistência a Podosphaera xanthii em meloeiro - Nunes, Elaíne Welk Lopes Pereira (2014)
Powdery mildew, caused by Podosphaera xanthii, is the most important foliar disease of cucurbits in the Northeast Brazil. Breeding for resistance is one of the best ways to control this pathogen. The objectives aims these work were to characterize morphologically and by microsatellites markers resistant accessions of melon, to study the inheritance and to identify SNP markers associated to resistance in the accessions AM55-1A and C-AC-15. Fifty-six melon plant accessions with different geographical origins were evaluated for resistance to P. xanthii using artificial inoculation procedure under greenhouse conditions. The resistant accessions C-AC-02, C-AC-09, C-AC-15, C-AC-34 and AM55-1A were characterized with morphological traits and microsatellites markers. The accessions C-AC-02, C-AC-09, C-AC-15, C-AC-34 exhibited characteristics of momordica botanical variety while the accession AM55-1A exhibited characteristics of acidulus botanical variety. The molecular characterization confirmed he results observed in morphological characterization. The inheritance of resistance in AM55-1A and C-AC-15 in crosses with susceptible cultivar Véndrantais was studied under greenhouses conditions. The segregations ratios for resistance/susceptibility observed in the different populations (F1, F2, BC1 and BC2) indicated a monogenic and dominant inheritance in AM55-1A and two independent genes with epispastic interaction double recessive control resistance in C-AC-15. The backcross population (BC1) derived from AM55-1A x Véndrantais and F2 population from C-AC-15 x Véndrantais were utilized to identify QTLs associated to resistance to P. xanthii using bulked segregation analysis with 243 SNP molecular markers. Two QTLs (Pm-AM55-1A_1 and Pm-A55-1A_2) were identified on ligation group V from AM55-1A x Véndrantais . One QTL (Pm-C-AC-15_5) on ligation group V and other (Pm-C-AC-15_9) on ligation group IX